ملامح عن تقلبات قيمة النقود بالأندلس في القرنين 5 و 6 الهجريين (11-12م) وتأثيراتها الإقتصادية و الاجتماعية - تجنانت, مراد (جامعة الوادي University of Eloued, 2017)
الملخص: تعد ظاهرة تَقَلُب قيمة النقود في العصور الوسطى خاصة ما ارتبط بوزنها ونسبة الذهب في الدنانير والفضة في الدراهم من أهم المؤثرات على النشاط المصرفي خاصة الإقتصادي عامة . ترتبط هذه التقلبات بالأطراف الفاعلة في الدولة و المجتمع كالحاكم و دور الضرب و الصرافون دون أن نغفل الدور السلبي المزورين. لقد أفرزت حالات تَغَيُرِ قيمة الصرف و التعدد النقدي مشاكل على صعيد المعاملات الاقتصادية و الاجتماعية حاول الفقهاء معالجها. غير أن مظاهر تذبذب قيمة العملة و ما ارتبط بها من آفات بقيت تساير الحياة الاقتصادية على الأقل في الفترة المدروسة. Fluctuations in the value of currencies in the Middle Ages were, above all, a phenomenon associated with their weights and the proportion of the precious metals in the different coins: gold in the dinar and silver in the dirham. This will surely influence currency and economic activities. These fluctuations are largely related to the decisions of the State, the minting houses, and currency exchanger. Without neglect the harmful role of counterfeiters.... The instability of the currencies values and their diversities in the économic operations had caused many disturbances which the doctors in Malikite jurisprudence had tryed to solve. However, these manifestations and their negatives consequences endured at the rhythm of economic life, at least during the period studied.
Keywords: الأندلس، قيمة النقود